Edmodo-Based Learning and the Students’ Perception - Andi Febriana Tamrin; Basri Basri (Makassar State University, 2020)
In the 4.0 era, technology is taking a part of many fields, including education. This research aimed is to find out about the perception of students about English class based on online method using Edmodo as medium. Descriptive qualitative method is used in this research. The respondents are the students who took English class and came from different department. This shows that the students preferred online method by using Edmodo for English Class. However, there is still drawbacks of using it.